Cryptography In Mathematics - Eshniyоzov A. I.; Murodova N. O. (Academia One Publishing, 2024)
The article discusses the main methods of cryptography and reveals their content. The work contains a step-by-step development of cryptography over the centuries. Attention is also paid to the relevance of this science in modern times
Keywords: cryptography; cryptographic methods; shorthand